Motivation Levels and Goals for the Practice of Physical Exercise in Five Different Modalities: A Correspondence Analysis - Borges, Juliana Correia; de Oliveira Filho, Gilson Gonçalves; de Lira, Claudio Andre Barbosa; da Silva, Ronaldo Angelo Dias; Alves, Eduardo da Silva; Benvenutti, Mateus Joacir; Rosa, João Paulo Pereira (Frontiers in Psychology, 2021)
The identification of the practitioner’s profile regarding their motivation level for physical exercise engagement could be a behavioral strategy to increase exercise adherence. The present study investigates the associations between motivation levels, modalities practiced and goals concerning the practice of physical exercise among physical exercise practitioners. A total of 100 physical exercise practitioners, of which 67 were women, took part in this study. The participants were engaged in extreme fitness program, strength training, fight training, Pilates, and functional training. Motivation level (BREQ-3) and expectations regarding regular physical exercise (IMPRAF-54) were assessed. A Multiple Correspondence Analysis demonstrating preferential relationships between descriptive and non-inferential variables. Strength training and fight training practitioners seek these modalities with the goals of "Health" and "Aesthetics," demonstrating low autonomy in relation to the behavior for the practice of physical exercise. Extreme Conditioning Program and Functional Training practitioners have as goal “Pleasure,” demonstrating medium and high levels of autonomy for such practice and Pilates practitioners have the goal of “Stress Control.” To promote and encourage the regular practice of physical exercise, this strategy could be used to take actions that increase the public's intention to start or continue in a physical exercise program.